The Effect of Financial Technology Adoption and Trust in the Government on Tax Compliance Among MSME Taxpayers, with Perceived Tax Fairness as a Mediating Variable (An Empirical Study of MSME Taxpayers at the Grogol Petamburan Local Tax Office) - Neissa Nur Fadhila (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
This study aims to determine the influence of the use of financial technology, and trust in the government on the compliance of MSME taxpayers with the perception of tax justice as an intervening variable. This study uses a causal method with a quantitative approach. The sample of this study is 125 respondents of MSME taxpayers registered at KPP Pratama Grogol Petamburan which were determined using the slovin formula with purposive sampling technique. The analysis techniques used were descriptive statistical analysis and partial lease square analysis, using the SmartPLS 4.0 application which was used to test the hypothesis. The results of the study show that the use of financial technology, and the perception of tax justice have a positive and significant influence on the compliance of MSME taxpayers. Trust in the government has no effect on the compliance of MSME taxpayers. The perception of tax justice can mediate the relationship between the use of financial technology and the compliance of MSME taxpayers. The perception of tax justice cannot mediate the relationship between trust in the government and the compliance of MSME taxpayers